Membranoproliferative Glomerulonephritis Type II (Dense Deposit Disease): An Update - Appel, Gerald; Cook, H. Terence; Hageman, Gregory; Jennette, J. Charles; Kashgarian, Michael; Kirschfink, Michael; Lambris, John D.; Lanning, Lynne; Lutz, Hans U.; Meri, Seppo; Rose, Noel R.; Salant, David J.; et al. (Journal of the American Society of Nephrology, 2005)
Membranoproliferative glomerulonephritis type II (MPGN II) is a rare disease characterized by the deposition of abnormal electron-dense material within the glomerular basement membrane of the kidney and often within Bruch’s membrane in the eye. The diagnosis is made in most patients between the ages of 5 and 15 yr, and within 10 yr, approximately half progress to end-stage renal disease, occasionally with the late comorbidity of visual impairment. The pathophysiologic basis of MPGN II is associated with the uncontrolled systemic activation of the alternative pathway (AP) of the complement cascade. In most patients, loss of complement regulation is caused by C3 nephritic factor, an autoantibody directed against the C3 convertase of the AP, but in some patients, mutations in the factor H gene have been identified. For the latter patients, plasma replacement therapy prevents renal failure, but for the majority of patients, there is no proven effective treatment. The disease recurs in virtually all renal allografts, and a high percentage of these ultimately fail. The development of molecular diagnostic tools and new therapies directed at controlling the AP of the complement cascade either locally in the kidney or at the systemic level may lead to effective treatments for MPGN II.
Gesehen am 15.02.2021